Advice from the health insurer as a channelling strategy: a natural experiment at a Dutch health insurance company - Romy E. Bes; Emile C. Curfs; Peter P. Groenewegen; Judith D. de Jong (BMC, 2018)
Abstract Background In a health care system based on managed competition it is important that health insurers are able to channel their enrolees to preferred care providers. However, enrolees are often very negative about financial incentives and any limitations in their choice of care provider. Therefore, a Dutch health insurance company conducted an experiment to study the effectiveness of a new method of channelling their enrolees. This method entails giving enrolees advise on which physiotherapists to choose when they call customer service. Offering this advice as an extra service is supposed to improve service quality ratings. Objective of this study is to evaluate this channelling method on effectiveness and the impact on service quality ratings. Methods In this experiment, one of the health insurer's customer service call teams (pilot team) began advising enrolees on their choice of physiotherapist. Three data sources were used. Firstly, all enrolees who called customer service received an online questionnaire in order to measure their evaluation of the quality of service. Enrolees who were offered advice received a slightly different questionnaire which, in addition, asked about whether they intended to follow the advice they were offered. Multilevel regression analysis was conducted to analyse the difference in service quality ratings between the pilot team and two comparable customer service teams before and after the implementation of the channelling method. Secondly, employees logged each call, registering, if they offered advice, whether the enrolee accepted it, and if so, which care provider was advised. Thirdly, data from the insurance claims were used to see if enrolees visited the recommended physiotherapist. Results The results of the questionnaire show that enrolees responded favorably to being offered advice on the choice of physiotherapist. Furthermore, 45% of enrolees who received advice and then went on to visit a care provider, followed the advice. The service quality ratings were higher compared to control groups. However, it could not be determined whether this effect was entirely due to the intervention. Conclusions Channelling enrolees towards preferred care providers by offering advice on their choice of care provider when they call customer service is successful. The effect on service quality seems positive, although a causal relationship could not be determined.